Breast milk to blood lead ratios among women from the West Bank of Palestine: a cross-sectional study of associated factors - Ramzi Shawahna (BMC, 2021)
Abstract Background Infants fed contaminated breast milk are at an increased risk of exposure to lead. Breast milk to blood (M/B) ratios have not been investigated among women in Palestine. The aim of this study was to assess blood, breast milk, and M/B lead ratios in samples collected from Palestinian breastfeeding women. Associations between sociodemographic characteristics with breast milk lead levels and M/B lead ratios were also investigated. Methods This study was conducted in a cross-sectional design in the period between October 2017 and April 2018. Breastfeeding women visiting maternity care centers in different regions of the West Bank of Palestine were recruited to the study by the nurses in the maternity care centers. Sociodemographic characteristics, venous blood, and breast milk samples were collected from each participant. Lead concentrations were analyzed using a validated inductively coupled plasma-mass spectrometric method. Mann-Whitney U test, Pearson's Chi-square, Fisher's exact, and Spearman's correlations were used to analyze the data. Odds ratios (OR) were computed using a multivariate logistic regression model. Results Matching blood and milk samples were collected from 80 women. Lead concentrations in 11 (13.8%) of the breast milk samples were above the World Health Organization's recommended levels. Breast milk lead levels were more likely to be ≥5 μg/L in breastfeeding women who lived in urban areas (aOR 4.96; 95% CI 1.10, 22.38) compared to those who lived in rural areas. Breast milk to blood lead ratios were more likely to be ≥25% in breastfeeding women who lived in urban areas (aOR 7.06; 95% CI 1.68, 29.77), used eye kohl (aOR 14.29; 95% CI 1.32, 155.06), and used hair dye (aOR 5.33; 95% CI 1.58, 18.00) compared to those who lived in rural areas, did not use eye kohl, and did not use hair dye, respectively. Conclusions Higher M/B lead ratios were predicted by living in urban areas, using eye kohl, and using hair dye. Decision makers in health authorities should address sources of exposure to lead in urban areas. Cosmetics containing lead should be assessed and regulated for lead content.